2017
DOI: 10.1257/pol.20150249
|View full text |Cite
|
Sign up to set email alerts
|

Does Money Matter in the Long Run? Effects of School Spending on Educational Attainment

Abstract: G overnment spending on primary and secondary education accounts for 4.3 percent of US GDP (National Center for Education Statistics 2013). Despite this large government investment, it remains unknown whether education spending improves students' long-run outcomes. One difficulty in answering this question is the lack of plausibly exogenous variation in spending. A second challenge is the necessity of high quality administrative data with which to track students over time, and especially past high school gradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 42 publications
3
101
4
Order By: Relevance
“…A key concern with policies that boost college-going is that they may induce marginal students to attend but not persist through college. This concern exists for any policy that increases college enrollment, such as Head Start (Deming, 2009), primary school class size reduction (Dynarski, Hyman, & Schanzenbach, 2013), or increases in school funding (Jackson, Johnson, & Persico, 2016;Hyman 2017b). However, the concern is even greater for light-touch policies, such as the one implemented in this study, because such interventions reduce informational and/or administrative hurdles to the college application process, but may not provide students with any lasting improvements in their skills or knowledge that can help them persist through college.…”
Section: College Persistencementioning
confidence: 99%
“…A key concern with policies that boost college-going is that they may induce marginal students to attend but not persist through college. This concern exists for any policy that increases college enrollment, such as Head Start (Deming, 2009), primary school class size reduction (Dynarski, Hyman, & Schanzenbach, 2013), or increases in school funding (Jackson, Johnson, & Persico, 2016;Hyman 2017b). However, the concern is even greater for light-touch policies, such as the one implemented in this study, because such interventions reduce informational and/or administrative hurdles to the college application process, but may not provide students with any lasting improvements in their skills or knowledge that can help them persist through college.…”
Section: College Persistencementioning
confidence: 99%
“…Increases 3 in instructional spending (e.g., class size) may play a role in the positive relationship between desegregation and Black student outcomes (Johnson, 2011;Reber, 2010). In addition, studies from the school finance reform literature found that court-ordered reforms led to increases in instructional expenditures, particularly through decreases in class size and student-teacher ratios (Hyman, 2017;Jackson et al, 2016;Lafortune et al, 2018). Increased instructional time as a result of smaller class sizes and higher quality teachers drawn by salary increases are thought to mediate the relationship between increased spending and improved outcomes (Jackson et al, 2016).…”
Section: School Spending and Student Outcomesmentioning
confidence: 99%
“…Critics of this view suggest that many papers in this literature do not deal adequately with the endogeneity problem and/or have problems with data quality. There are indeed more papers with a strong methodology (using natural or real experiments) that show a positive effect from resource-related factors including Angrist and Lavy's (1999) study on the effect of class size in Israel; studies on the experimental Tennessee STAR class size reduction (Krueger 1999;Krueger and Whitmore 2001;Chetty et al 2011); studies that have made use of student finance reforms (Guryan 2001; Van der Klaauw 2008a;Bénabou et al 2009;Roy 2011;Hyman 2016;Jackson et al 2016); and some of Hanushek's own work (Rivkin, Hanushek and Kain 2005). There have also been a couple of recent papers in England that have found modest effects of increased school resources (Jenkins et al 2006;Holmlund et al 2010;Machin et al 2010).…”
Section: Introductionmentioning
confidence: 99%